2013
DOI: 10.1109/tmm.2013.2240286
|View full text |Cite
|
Sign up to set email alerts
|

On the Investigation of Cloud-Based Mobile Media Environments With Service-Populating and QoS-Aware Mechanisms

Abstract: Abstract-Recent advances in mobile devices and network technologies have set new trends in the way we use computers and access networks. Cloud Computing, where processing and storage resources are residing on the network is one of these trends. The other is Mobile Computing, where mobile devices such as smartphones and tablets are believed to replace personal computers by combining network connectivity, mobility, and software functionality. In the future, these devices are expected to seamlessly switch between… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
31
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 56 publications
(31 citation statements)
references
References 9 publications
0
31
0
Order By: Relevance
“…Service Management Platform: The service management platform deals with how services are registered in a cloud which also includes the overall service and Security Level Agreement (SSLA) between the service providers and the cloud providers as well as stores the record of unique service ID that has been assigned to each service [50].…”
Section: Key Mechanisms For Providing Possible Solutions To Manage Mhmentioning
confidence: 99%
See 1 more Smart Citation
“…Service Management Platform: The service management platform deals with how services are registered in a cloud which also includes the overall service and Security Level Agreement (SSLA) between the service providers and the cloud providers as well as stores the record of unique service ID that has been assigned to each service [50].…”
Section: Key Mechanisms For Providing Possible Solutions To Manage Mhmentioning
confidence: 99%
“…In order to achieve this requirement, each service must provide a list of parameters which must be agreed with those parameters obtained by the cloud. This parameter list is also used to migrate the service in order to find appropriate clouds that can accept the service [50]. The Secure Transactional Layer will secure the remote procedure between stakeholders and cloud server by applying an authentication mechanism.…”
Section: Developing the New Security Frameworkmentioning
confidence: 99%
“…Fragkiskos et al [4] introduced a layered architecture system that relates to OSI layers model for cloud resources management in provision better QoS for multimedia applications. The proposed SPM mechanism have multiple features in QoS provisioning.…”
Section: Qos Metrics For Cloudy Multimedia Evaluationmentioning
confidence: 99%
“…MCC is a model developed as a solution to overcome the challenges in mobile devices using CC services like storage and computing resources [2][3]. Experience with Internet-based services has shown that attacks from worms and viruses such as Code Red and SQL Slammer are common threats to network-oriented applications.…”
Section: Introductionmentioning
confidence: 99%